A profile of the popular entrepreneur: a value-based approach. Issue 2 (3rd June 2019) - Esqueda H., Sofia; Csoban, Eugenia; Felipe Prat, Jose
Abstract : Purpose: The purpose of this paper is to identify the personal characteristics and individual values of Venezuelan low-income entrepreneurs, according to the theoretical framework of the Schwartz model. Design/methodology/approach: A stratified probabilistic sample of 416 individuals was selected from a database of Bangente's clients, who received microcredits between 1999 and 2016, in the Capital District of Venezuela. The Portrait Value Questionnaire (Schwartz, 2003 ;Peiró and Palencia, 2009 ) was applied to measure the values of power, self-direction, stimulation and achievement. The locus of control was measured (Schjoedt and Shaver, 2012 ) and information was collected on some personal variables. An analysis of hierarchical clusters was conducted to group clients with similar characteristics, as well as a discriminant analysis, to characterize the groups obtained. Findings: The selected Schwartz values, the locus of control and personal characteristics (such as educational level, age and gender) proved to be efficient in discriminating between four groups or profiles of low-income entrepreneurs: those "Focused on progress through effort, " "Independent and ambitious young people, " those "Focused on power and achievement" and those who were "Indifferent." The results of the cluster analysis were validated using discriminant analysis, which identified the variables with the greatest impact for the characterization of each group. The coefficients of the discriminant functions would allow the classification of a new individual requesting a microcredit into one of the groups obtained. This is a proposal to complement the selection process mechanisms currently used to decide whether or not to grant loans, which must be validated in conclusive studies. Research limitations/implications: The results cannot be generalized until the study is replicated in representative samples in other entities of the microfinance sector. Originality/value: The main contribution of this work is the integration of individual values in the profile description of low-income entrepreneurs and in the use of statistical strategies such as cluster analysis and discriminant function. The nature of the study is exploratory: the development of this line of research can guide future decisions about which clients (according to their values, personal characteristics and locus of control) could receive their financial support. When considering these non-traditional variables in the banking context, the aim is to enrich our knowledge about low-income entrepreneurs. Abstract : Propósito: El objetivo de este trabajo es identificar cuáles son las características personales y los valores individuales de los emprendedores populares venezolanos, según el marco teórico del modelo de Schwartz. Diseño/Metodología/Enfoque: Se seleccionó una muestra probabilística estratificada de 416 individuos, de una base de datos de clientes de Bangente beneficiarios de microcréditos entre 1999 y 2016, del Distrito Capital de Venezuela. Se aplicó el Portrait Value Questionnarie (PVQ) (Schwartz, 2003 ;Peiró y Palencia, 2009 ) para medir los valores poder, autodirección, estimulación y logro. Se midió el locus de control (Schjoedt y Shaver, 2012 ) y se recopiló información sobre algunas variables personales. Se llevó a cabo un análisis de conglomerados jerárquicos para agrupar clientes con características similares y un análisis discriminante para caracterizar los grupos obtenidos. Resultados: Los valores de Schwartz seleccionados, el locus de control y las características personales (como nivel educativo, edad y género) mostraron ser eficientes para discriminar de forma significativa entre cuatro grupos o perfiles de emprendedores populares: "orientados al progreso por esfuerzo, " "jóvenes independientes y ambiciosos, " "focalizados en el poder y logro" e "indiferentes." Los resultados del análisis de conglomerados fueron validados por análisis discriminante, que permitió identificar las variables de mayor impacto para la caracterización de cada grupo. Los coeficientes de las funciones discriminantes permitirían clasificar a un nuevo individuo solicitante de microcréditos en alguno de los grupos obtenidos; esta es una propuesta complementaria a los mecanismos de selección actualmente utilizados para decidir la concesión de los créditos, que deberá ser validada en estudios concluyentes. Limitaciones de la investigación/implicaciones: No se pueden generalizar los resultados hasta que el estudio se replique en muestras representativas en otras entidades del sector microfinanciero. Originalidad/valor: La mayor contribución de este trabajo está en la integración de los valores individuales en la descripción del perfil de los emprendedores populares y en el uso de estrategias estadísticas como el análisis de conglomerados y la función discriminante. La naturaleza del estudio es exploratoria: el desarrollo de esta línea de investigación puede orientar en el futuro las decisiones acerca de a cuáles clientes (de acuerdo con sus valores, características personales y locus de control) podrían dirigir su apoyo financiero. Al considerar estas variables no tradicionales en el contexto de la banca, se pretende enriquecer el conocimiento sobre los emprendedores populares.